The influence of sulfur on the machinability of gray cast iron FC25 - Pereira A.A. (2006)
The present research deals with the influence of sulfur on gray cast iron machinability. Tupy Fundições produced the workpiece materials in usual commercial manufacturing conditions with sulfur levels raging from 0.065 to 0.18%. The influence of different of sulfur contents on gray cast iron machinability was studied for turning operation at 100, 150 and 200 m/min cutting speeds. Uncoated cemented carbide tools were used, and 'flank wear' assessment criterion was applied. The sulfur increase from 0.065 to 0.18% did not produce significant alteration on mechanical properties nor on material microstructures. It was verified that for an effective reduction of the adhesive wear during the machining the smallest area occupied by the manganese sulfide must be (18 ± 6) × 10-3%. The machinability of gray cast iron FC25 with 0.12, 0.15 and 0.18% of sulfur does not differ significantly when machined at 150 and 200 m/min. In relation to gray cast iron FC25 with 0.12% of sulfur, the material with 0.065% S presented a tool life reduction of 24, 32 and 38%, for the speeds 100, 150 and 200 m/min, respectively. From this research, important results were obtained, becoming viable the use of a higher sulfur percentage on gray cast iron FC25 production, without the detriment of mechanical properties, microstructure and machinability. © 2006 Elsevier B.V. All rights reserved.